5g+4(-5+3g)=1-9

Simple and best practice solution for 5g+4(-5+3g)=1-9 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5g+4(-5+3g)=1-9 equation:


Simplifying
5g + 4(-5 + 3g) = 1 + -9
5g + (-5 * 4 + 3g * 4) = 1 + -9
5g + (-20 + 12g) = 1 + -9

Reorder the terms:
-20 + 5g + 12g = 1 + -9

Combine like terms: 5g + 12g = 17g
-20 + 17g = 1 + -9

Combine like terms: 1 + -9 = -8
-20 + 17g = -8

Solving
-20 + 17g = -8

Solving for variable 'g'.

Move all terms containing g to the left, all other terms to the right.

Add '20' to each side of the equation.
-20 + 20 + 17g = -8 + 20

Combine like terms: -20 + 20 = 0
0 + 17g = -8 + 20
17g = -8 + 20

Combine like terms: -8 + 20 = 12
17g = 12

Divide each side by '17'.
g = 0.7058823529

Simplifying
g = 0.7058823529

See similar equations:

| x-41=-58 | | 6x-5=-8X-2 | | -4=5+2n-1 | | 3a+30=6a | | 4(20-n)=4 | | x^2+5-3x=0 | | 15k-3=4+6k | | 12x=4(7+24) | | 20a^2+5a=0 | | -12x=4(7+24) | | 2+2x=x+14 | | 8=3(3c+5) | | 16k+35= | | 5(n+1)+10=20 | | 6y-3=6y+18 | | 3x+4=x+24 | | -22=7(1+3v)-8 | | .5a-9=4a+5 | | 5(n+2)=30 | | 5g-15=3(-5) | | 0.02+0.01=0.005 | | 2(10-n)=6 | | -5a+2a= | | 5(1+7a)-2a=38 | | 4x+1=20x-47 | | 4(n-1)=20 | | -7d+6=-12 | | 5+5=a | | -7+6=-12 | | 3(n+1)=20 | | 3(2x+7)=57 | | 1y-5=y+9 |

Equations solver categories